Tonality of low-frequency synthesized piano tones - CUDDY, Lola L.; RUSSO, Frank A.; GALEMBO, Alexander (Archives of Acoustics, 2007)
The influences of inharmonicity and bandwidth on sensitivity to tonality in the low-frequency range (A0 to G#1) were tested in a listening experiment. Participants were presented a key-defining context (do-mi-do-so) and were asked to rate the goodness of fit of probe tones to the context. Probe tones were the 12 tones of the chromatic scale beginning on do. The set of 12 ratings, called the probe-tone profile, was compared to an established standardized profile for the Western tonal hierarchy. Prior research employing this method with real (sampled) piano tones has suggested that sensitivity to tonality is influenced by inharmonicity, particularly in the lowest octaves of the piano where inharmonicity levels are substantially above the detection threshold. In the present experiment, sensitivity to tonality was tested using synthesized piano-like tones that were either harmonic or inharmonic. Participants were tested in either a broadband (no filtering) or low-pass (low-pass filtered at 1 KHz) condition. Sensitivity to tonality was highest in the broadband harmonic condition followed by the broadband inharmonic condition. No sensitivity to tonality was found for the low-pass conditions; rather, for both harmonic and inharmonic tones, participants rated probe tones as increasingly good fit as pitch distance from do decreased.